WISATA OUTBOUND DI KOTA SINGKAWANG - Setiarini, Dini Asih; Muazir, Syaiful; Khaliesh, Hamdil (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
The decline in performance of both private and public employees is getting worse day by day. The worsening of the employee's performance had a big impact on the agency. There are various ways that can be done to improve the performance, one of the effective ways to do is to conduct training as well as travel tours. This training and tour is usually known as outbound. Apart from being able to be done by employees or outbound employees, it is usually also carried out from various circles, from school and college children as well as from the general public. Outbound is a form of learning all applied sciences that is simulated and carried out in an open or closed environment with an effective form of play, which combines intelligence, physical and mental. Outbound is a management training which is a combination of outdoor sports, dexterity and adventure games with the concept of nature which aims to shape, direct, convey a vision, as well as have recreation for the participants. Singkawang City is a city famous for its various tourist destinations. In addition, in Singkawang City, there are areas that have the potential to be built for Outbound Tourism. Outbound tourism in Singkawang City not only facilitates games, but there are camping and other supporting facilities.